Robotics, automation, and control in industrial and service settings - Luo, Zongwei, 1971- (Engineering Science Reference, 2015)
"This book meets the challenges presented by the rise of ubiquitous computing by providing a detailed discussion of best practices and future developments in the field of automation and robotics"-- Provided by publisher.
"Premier reference source."
Keywords: Automation.; Robotics.; Service industries -- Information technology.; elektronické knihy; electronic books